Gut microbiota, physical activity and/or metabolic markers in healthy individuals - towards new biomarkers of health - Myhrstad, Mari C. W.; Ruud, Emilia; Gaundal, Line; Gjøvaag, Terje; Rud, Ida; Retterstøl, Kjetil; Ulven, Stine M.; Holven, Kirsten B.; Koehler, Karsten; Telle-Hansen, Vibeke H. (Frontiers in Nutrition, 2024)
The global prevalence of the metabolic disease Type 2 Diabetes (T2D) is increasing. Risk factors contributing to the development of T2D include overweight and obesity, lack of physical activity (PA), and an unhealthy diet. In addition, the gut microbiota has been shown to affect metabolic regulation. Since T2D is preventable, efforts should be put into the discovery of new biomarkers for early detection of individuals at risk of developing the disease. T2D is preventable and efforts should be put into the discovery of new biomarkers and early detection of individuals at risk of developing the disease.The objective of the cross-sectional study was to explore the relationship between gut microbiota and physical activity (PA) and, gut microbiota, and and/or metabolic markers such as selected amino acids (AA), markers of glycaemic regulation and lipid metabolism and anthropometric measures.Design: Healthy adults (18 and 65 years) with BMI between 18.5 and 27.5 kg/m2 originally recruited to a randomised controlled trial (RCT) (n=17: six males, eleven females), were included in this exploratory cross-sectional study. PA Physical activity data was calculated based on a 3-days registration, and blood metabolome, gut microbiota analyses and anthropometric measures from one visitthe start of the intervention were used in this cross-sectional study.Results: Of the 47 gut bacteria analysed, there were a total of 87 significant correlations with AA, PA, body composition and/or metabolic markers. Several of the gut bacteria correlated with both PA, and metabolic and/or anthropometric markers.In this study, we demonstrate associations between gut bacteria and PA and/or, metabolic markerstes including AA and gut bacteria in healthy individuals. The results may guide future studies aiming at identifying new and early biomarkers of metabolic health and diseases.